Aux origines des pharaons noirs : 10'000 ans d'archéologie en Nubie - Honegger, Matthieu, (Laténium : Fondation Kerma, 2014)
Materials in the exhibition are the result of archaeological digs conducted in and near Kerma, Sudan by Swiss teams from the Université de Genève beginning in 1964, under Charles Bonnet, then from 2002 under Matthieu Honegger, Université de Neuchâtel.